Clinical Spectrum of Poisoning in Pediatric Emergency in Underdeveloped Countries - Razi ur Rahman (Saudi Journal of Emergency Medicine)
Background: Poisoning is a common presentation in pediatric emergency. Over the period, clinical spectrum changes continuously. This study helps to understand current spectrum of poisoning in pediatric population. Objective: To find out the clinical spectrum of Poisoning in pediatric population in Pediatric Emergency Department of underdeveloped country. Method: We did a cross-sectional study in eleven units of pediatric emergency of tertiary care hospitals of Pakistan during a period of six months from January 2022 to June 2022. Result: A total of 631 Patients evaluated who presented to PED in this duration. The mean age of presentation is 42.15 months with a male to female ratio of 1:1.3. In almost 80.03 % (n=505) cases the cause of poisoning in unknown, it is because proper history is not available. Out of known ingestion (n= 126), 56.34 (n=71) is due to Organophosphate ingestion, Benzodiazepine 18.25 % (n=23), Salicylate 10.31 % (n=13), Vitamin supplements 9.52 % (n=12) and Tricyclic antidepressant 5.55 % (n=7). Most 33.12 % (n=209) were discharged home with a length of stay of 7.58 hours, 26.94 % Left Against Medical Advice, 25.51 % (n=170) were discharged on request, 2.53 % (n=16) referred to other h hospital due to unavailability of bed and Four patients were expired. The expired patients were all presented with unknown poisoning, length of stay was 12.06 %, the average age was 41.6 Months. Conclusion: Public awareness is needed to decrease the morbidity and mortality due to unknown poisoning, so pediatric patients can get better treatment. [SJEMed 2024; 5(1.100): S2-S2]